The utilization of digital fault recorders in protection, system analysis on Tenaga Nasional Berhad transmission system - Mohd. Zin, Abdullah Asuhaimi (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 445 HOES LANE, PISCATAWAY, NJ 08855 USA, 2007)
The protection system is a very critical element in a power system. It is security to the power system for isolating only, the faulty plant as fast as possible. A simple fault can lead to a cascade of tripping if it is not isolated accurately and fast enough by the, protection system. Furthermore, protection system analysis is a complicated task for inexperienced engineers. Most of the analysis relied mainly on the relay indications which could lead to incorrect analysis due to the uncertainty of the correct relay operations and time tagging. Therefore, I it is an urgent requirement to explore protection system analysis to improve system reliability. This paper describes a method of early detection of protection system failures in Tenaga Nasional Berhad's Transmission Grid using digital fault recorders. The method has demonstrated to be more accurate, thus enabling faster decision making and shorter interruption time.